The Effect of Exercise on the Skin Content of the Reduced Form of NAD and Its Response to Transient Ischemia and Reperfusion in Highly Trained Athletes - Bugaj, Olga; Zieliński, Jacek; Kusy, Krzysztof; Kantanista, Adam; Wieliński, Dariusz; Guzik, Przemysław (Frontiers in Physiology, 2019)
Reduced nicotinamide adenine dinucleotide (NADH) is synthesized in the cellular nucleus, cytoplasm and mitochondria but oxidized into NAD+ almost exclusively in mitochondria. Activation of human skin by the 340 nm ultraviolet light triggers natural fluorescence at the light length of 460 nm, which intensity is proportional to the skin NADH content. This phenomenon is used by the Flow Mediated Skin Fluorescence (FMSF) which measures changes in the skin NADH content during transient ischemia and reperfusion. In this study we examined the effects of exercise to exhaustion on the skin changes of NADH in response to 200-second forearm ischemia and reperfusion in 121 highly-trained athletes (long-distance running, triathlon, taekwondo, rowing, futsal, sprint running, fencing, and tennis). We found that exercise until exhaustion changes the skin content of NADH, modifies NADH turnover at rest, during ischemia and reperfusion in the most superficial living skin cells. Compared to the pre-exercise, there were significant increases in: mean fluorescence recorded during rest as the baseline value (Bmean) (p<0.001), the maximal fluorescence that increased above the baseline during controlled forearm ischemia (FImax) (p<0.001), the minimal fluorescence after decreasing below the baseline during reperfusion (FRmin) (p<0.001) and the difference between Bmean and FRmin (Rmin) (p=0.001), and reductions in the difference between FImax and Bmean (Imax) (p<0.001) and Imax/IRampl ratio (CImax) (p<0.001) after the incremental exercise test. There was no statistical difference between pre- and post-exercise the maximal range of the fluorescence change during ischemia and reperfusion (IRampl) (p=0.261). In conclusion, exercise to exhaustion modifies the skin NADH content at rest, during ischemia and reperfusion as well as the magnitude of changes in the NADH caused by ischemia and reperfusion. Our findings suggest that metabolic changes in the skin NADH accompanying exercise extend beyond muscles and affect other cells and organs.